2018
DOI: 10.2147/cmar.s172332
|View full text |Cite
|
Sign up to set email alerts
|

Expressions and prognostic values of the <em>E2F</em> transcription factors in human breast carcinoma

Abstract: E2F transcription factors (E2Fs) are a family of transcription factors involved in cell proliferation, differentiation, and apoptosis. Their important roles in the development and metastasis of breast carcinoma (BC) have been discovered by previous in vitro and in vivo studies. Yet, expressions and distinct prognostic values of these eight E2Fs in human BC remain unclear in many respects. In this study, we aimed to reveal their roles in BC through analyzing the transcription and survival data of the E2Fs in BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…By ROC curve analysis, blood E2F3 mRNA was able to effectively distinguish PTC from benign hyperplasia diseases and normal tissue at a cut off 2.30. These ndings were in close agreement with previous studies that demonstrated that peripheral blood E2F3 mRNA may be a diagnostic marker in lung, breast and prostate cancer [18,19,26,31,33,34].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…By ROC curve analysis, blood E2F3 mRNA was able to effectively distinguish PTC from benign hyperplasia diseases and normal tissue at a cut off 2.30. These ndings were in close agreement with previous studies that demonstrated that peripheral blood E2F3 mRNA may be a diagnostic marker in lung, breast and prostate cancer [18,19,26,31,33,34].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, E2F3 plays an important role in determining the time of the G1/S transition and the rate of DNA synthesis [24,25]. Early studies demonstrated that E2F3 is oncogenic in various human cancers, including breast, bladder, lung and prostate cancer [18,19,26]. E2F3 is essential in promoting the proliferation of ovarian cancer cells by initiating integral signaling of the EGFR-driven cell response [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the E2F transcription factor is one of the key regulators of cell cycle progression and triggering apoptosis [30]. Also, alterations of E2F may be associated with shorter survival of cancer patients [31]. Moreover, the E2F1 member of the E2F family is associated with metastasis of cancer cells [32].…”
Section: Kinase Mirna and Transcription Factor Target Network Corrementioning
confidence: 99%
“…Additionally, E2F3 has played a key role in diverse biological processes such as lens development, cardiac neovascularization, DNA damage responses, neuronal migration, and myogenesis [6,13,[17][18][19][20][21]. Dysregulation of E2F3 is closely related to carcinogenesis, and recent studies confirmed that overexpression of miRNAs targeting E2F3, inhibits cell migration and proliferation in many tumors [22][23][24][25][26][27][28]. E2F3 is considered a promising prognostic marker in specific carcinomas [27,29,30].…”
Section: Introductionmentioning
confidence: 99%